Hubungan Tingkat Kepuasan Pasien Rawat Jalan terhadap Pelayanan Kesehatan di Klinik Pratama Elvi Diana Kelurahan Kuala Bekala Medan Johor - Nasution, Dian Permata; Napitu, Marolop Parlindungan; Purba, Yeni Trisna; Ginting, Isaharpika Br; Hasibuan, Jesicca (Jurnal Riset Hesti Medan, 2025)
Service quality is one of the key factors that determine patient satisfaction in healthcare services. This study aims to analyze the relationship between service quality and patient satisfaction at a Community Health Center (Puskesmas) using the five SERVQUAL dimensions: tangible, reliability, responsiveness, assurance, and empathy. This research employed a quantitative design with a cross-sectional approach. A total of 54 respondents were selected using a purposive sampling technique. Data were analyzed using the Chi- Square test.The results showed that service quality had a significant relationship with patient satisfaction across all SERVQUAL dimensions, namely tangible (p = 0.006), reliability (p = 0.015), responsiveness (p = 0.015), assurance (p = 0.006), and empathy (p = 0.004). The majority of respondents assessed the overall service quality as good (61.1%), yet dissatisfaction remained in several aspects, particularly in physical facilities, timeliness, responsiveness, and healthcare workers’ personal attention. This study concludes that service quality has a significant association with patient satisfaction, although gaps were found between patients’ perceptions of service quality and their satisfaction in some dimensions. It is recommended that the health center improve facilities and infrastructure, strengthen staff responsiveness and empathy, and optimize communication skills and professionalism among healthcare workers to enhance overall patient satisfaction.